Frekwencja wyborcza a stan polskiej demokracji - Panicz, Urszula (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Last local election showed that the voter turnout in Poland is low and not everybody wants to participate in election. This article tries to find the causes of this situation in Poland while underlining the importance of turnout. What is more, the aim of this article is to show that increasing the number of people who vote is quite difficult. It is caused by so many various reasons.